Forms of tourist and local studies work in Kharkiv region during the martial state - Skryl, Iryna; Dobrovolska, Nataliia; Kandyba, Yurii (Human Geography Journal, 2024)
The article analyzes the peculiarities of tourism and local studies work in Kharkiv region in the conditions of military aggression of the Russian Federation. The authors characterized the main directions of the organization of educational activities of extracurricular educational institutions and highlighted national-patriotic and tourist-local studies among them. The analysis of the dynamics of the tourist and local studies activities of schoolchildren manifested that the number of clubs and their students decreased by more than half in Kharkiv region during 2019 - 2023.In the structure of tourist and sports clubs, the largest share of pupils falls on hiking tourism, bicycle tourism, sports tourism, and sports orientation. Among tourist and local studies clubs, the most pupils attend clubs in the field of scientific research, environmental local studies, ethnology, historical and geographical local studies.As a result of the military aggression of the Russian Federation in Kharkiv region (excluding the regional center), more than 30% of extracurricular education institutions were damaged or ceased to function due to hostilities or occupation. The institutions of the Kupyansk district were the most affected, where none of the five extracurricular education institutions are currently operating. Three out of 6 extracurricular education centers operate in Izyum district, 6 out of 9 in Kharkiv district, 5 out of 6 in Loziv and Bogodukhiv districts, 7 out of 8 in Chuguyiv district, and all 6 centers operate in Krasnograd district.The priority areas of extracurricular education in Kharkiv region should be national-patriotic and military-patriotic education, which is extremely relevant in the conditions of military aggression of the Russian Federation. In the de-occupied territories, it is necessary to restore centers of extracurricular education institutions and develop local studies work with schoolchildren.